Valuing hearing-related changes in health-related quality of life - Williams, Natalie Jade (2020)
Within healthcare systems different areas of healthcare compete for limited resources. Allocating resources across healthcare programmes efficiently requires accurate, verifiable, robust methods. To ensure optimum resource allocations health conditions must be evaluated, taking into account their effects on quality of life, and the cost of receiving treatments. However, before a health state can be evaluated it must first be described to the individual valuing it, in order for an individual to know exactly what they are evaluating. With hearing loss, as with many other medical conditions, it is difficult to describe the impact of having a hearing loss on quality of life, either using general health dimensions or with words alone. This research aims to explore alternative methods of describing hearing-related heath states that have been prompted by recent advances in health valuation.